(untitled) (Olhar de Professor, 2023)
This article presents partial results of a research developed at doctoral level, more specifically, of the documental analysis carried out on Pedagogical Projects (PP) of four Pedagogy courses located in the state of Bahia, as well as semi-structured interviews carried out with their coordinators, where it was sought to realize what place the epistemological debate about Pedagogy as a knowledge field occupies in the scope of the pedagogical-curricular proposal and in the daily formative actions inside these graduation courses. Theoretically, the research is based on the studies of Libâneo (2010), Pimenta (2021), Franco (2008), Saviani (2008) and Silva-Junior (2019), which converge in the defense of the epistemological specificity of Pedagogy as Science of Education. The results indicate that the discussion about Pedagogy regarding its epistemic dimension occupies an embryonic place within the researched courses, raising the need for a more dense debate at national level about this historical problematic in the Brazilian scenario.